Durability of platinum-based fuel cell electrocatalysts: Dissolution of bulk and nanoscale platinum - Cherevko, Serhiy; Kulyk, Nadiia; Mayrhofer, Karl (Nano Energy, 2016)
Platinum- and platinum-alloy-based electrocatalysts are the key component of the state-of-the-art proton exchange membrane fuel cells. Dispersed in the form of nanometer size particles on a high surface-area carbon support and subjected to highly corrosive environment, they can degrade and lead to fuel cell performance deterioration with time. This review is a survey of recent literature of platinum dissolution - a constituent part of the complex degradation mechanism of fuel cell electrocatalyst. The focus is set on two types of surfaces: extended and nanoparticulate. Results obtained on extended surfaces of model bulk electrodes provide fundamental insights into mechanisms of equilibrium and non equilibrium platinum dissolution. This knowledge can be used for the comprehension of platinum dissolution from nanostructured electrodes, both in half-cell aqueous electrolyte and fuel cell environment. Detailed analysis realized in the current work shows that model systems suit well the trends in dissolution of real catalysts. Moreover, dissolution behavior in real fuel cells is portrayed well by half-cell dissolution tests. Peculiarities in dissolution of nanoparticles, especially in the real fuel cell environment are discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell; Electrocatalysis; Nanoparticles; Degradation